Consortium ercto non cito w Noctes Atticae Aulusa Gelliusa - Zabłocki, Jan (Prawo Kanoniczne, 1988)
Initially after the death of patris familias siblings created a community called ercto non cito. The name of this institution, that is ercto non cito appears only in Gellius’ (Gell. 1.9.12) and Servius’ (ad Aen. 8. 642—643). Whereas in the corresponding text of Gaius (G. 3. 154 a) appearing in that place lacuna was supplemented in editio princeps (PSI XI. 1182) with the words erctum non citum. Similar wording erctum citumque can be found in Festus (L. 72) and is likely to be found in Quintilianus (Inst. 7.3.13), while erctum cieri occurs in Cicero (de orat. 1.56.237). Gellius compares consortium ercto non cito with inseparabilis societas of Pitagoreans. Such comparison gives rise to a problem whether antiquum consortium was inseparabile or inseparabilis societas was like ancient consortium. The analysis of the above mentioned sources allows us to assume that erctum is used to mean hereditas destined for division, while citum signifies the activity of dividing hereditas. Thus the phrase ercto non cito would signify duration, and not division of hereditas, which is destined for the division, whereas the phrase erctum citumque (erctum cieri) signifies hereditas in the course of its dividing. As a result it can be stated that assimilation of consortium ercto non cito to societas of Pitagoreans seems not to be justified and moreover it is contrary to the corresponding sources, which treat consortium ercto non cito as community, though not divided but destined for the division. It serves temporarily the purpose of keeping the community of persons and things which existed during patris familias life also after his death.